S. 33 and H.R. 1753, the Methane Hydrate Research and Development Act of 1999 : hearing before the Subcommittee on Energy and Environment of the Committee on Science, House of Representatives, One Hundred Sixth Congress, first session, May 12, 1999. - United States. Congress. House. Committee on Science. Subcommittee on Energy and Environment. (Washington : U.S. G.P.O. : For sale by the U.S. G.P.O., Supt. of Docs., Congressional Sales Office, 1999)
"Serial no. 106-14." Shipping list no.: 2000-0025-P. Distributed to some depository libraries in microfiche. Includes bibliographical references. Mode of access: Internet.